Armed Conflict in Central America and Immigrant Health in the United States - Jeremy C. Green; Rhonda BeLue; Eric A. Boakye; Esther Choi; Michael G. Vaughn (Ubiquity Press, 2018)
Background: While many researchers document the immediate and localized health effects of armed conflicts on combatants are well documented in the literature, less is known about the effects of armed conflict on individuals who have subsequently migrated elsewhere. Objective: This study aims to estimate associations between pre-migration armed conflict in Central America and post-migration health in the United States. Methods: We created a new dataset that combines information on armed conflicts in Central America and immigrant health in the United States. We used ordered probit regressions to estimate age-adjusted associations between pre-migration armed conflict and post-migration health. Findings: The study sample of Central American immigrants included 15,563 females and 16,236 males between the ages 15 and 69. The mean age was 37.2 years (standard deviation, 11.6 years) for females and 35.5 years (standard deviation, 11.2 years) for males. After adjusting for age, pre-migration armed conflict was associated with a 8.6 percentage point decrease in excellent health for females (95% confidence interval, 6.0 to 11.1), and a 7.3 percentage point decrease for males (95% confidence interval, 4.0 to 10.7). Each decade of pre-migration armed conflict was associated a 2.9-percentage point decrease in excellent health for females (95% confidence interval, 2.0 to 3.8) and a 1.6-percentage point decrease for males (95% confidence interval, 0.6 to 2.6). For those individuals exposed to armed conflict, each decade since the most recent armed conflict was associated with a 1.5 percentage point increase in excellent health for females (95% confidence interval, 0.4 to 2.5). For males, the average marginal effect of decades since last conflict was not statistically significant (95% confidence interval, -0.001 to 0.002). Conclusions: Pre-migration armed conflict in Central America is associated with decreases in excellent post-migration health in the United States. The effects of armed conflict are cumulative and fade over time for females.